2016
DOI: 10.1016/j.biomaterials.2016.01.046
|View full text |Cite
|
Sign up to set email alerts
|

The two faces of metal ions: From implants rejection to tissue repair/regeneration

Abstract: The paradigm of metallic ions as exclusive toxic agents is changing. During the last 60 years, knowledge about toxicological and immunological reactions to metal particles and ions has advanced considerably. Hip prostheses, namely metal-on-metal bearings, have prompted studies about excessive and prolonged exposure to prosthetic debris. In that context, the interactions of metal particles and ions with cells and tissues are mostly harmful, inducing immune responses that lead to osteolysis and implant failure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(61 citation statements)
references
References 219 publications
3
55
1
2
Order By: Relevance
“…Specifically, Mg1Zr2Sr2.08Dy exhibited a lower corrosion rate in SBF, and it also showed relatively higher cell viability compared with the other Mg alloys. This is in agreement with a report that the release rate of the metallic ions greatly affects the biosafety of an implant material …”
Section: Discussionsupporting
confidence: 93%
“…Specifically, Mg1Zr2Sr2.08Dy exhibited a lower corrosion rate in SBF, and it also showed relatively higher cell viability compared with the other Mg alloys. This is in agreement with a report that the release rate of the metallic ions greatly affects the biosafety of an implant material …”
Section: Discussionsupporting
confidence: 93%
“…Co is considered as a toxic agent in most studies but might in sub‐toxic concentrations promote angiogenesis as suggested in a review by Vasconcelos et al50 In the present study, neither Co nor Cr addition impaired cell viability as compared with Ti alone. This is supported by a previous study where Co not affected the viability of THP‐1 cells in concentrations up to 200 µM 31.…”
Section: Discussioncontrasting
confidence: 38%
“…Alternatively, materials containing therapeutic ions are drawing attention regarding effective use in bone a Institute of Biomaterials, Department of Materials Science and Engineering, regeneration, as these materials can release therapeutic ions and thus lead to positive biological responses depending on the type and amount of released ions. 7,8 Among a large number of ions with therapeutic effects, zinc (Zn), being an important element of alkaline phosphatase (ALP) and a key mediator of bone matrix mineralization, 9 plays a significant role in bone formation. 10,11 Additionally, Zn ions show antibacterial effects, being therefore beneficial for the inhibition of infection.…”
Section: Introductionmentioning
confidence: 99%